(3JGQjN bQjT hCSeGFges ((3OQhjT eMehO Hf YHOGdbGOQ Hf eMehO Hjc s)
(3ChdgG (B:s
(3CeG HYO , agPG eNJUQ PcQJ ajg fSH fHjfG eMeO Udi Ydjg hSde , hGHJOCJ Hef jdjg ef Cgdg GdCOfi s
(3BNQgG (B:s
(3CHh OdGeI hCHh YWGA GdSfOj GdTGYQGf s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B82 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs